Multivalent mRNA vaccine platform with compatible antigens conferred broad-spectrum protection against orthoebolaviruses’ exposure - Jiachen Zhang; Xinghai Zhang; Yanfeng Yao; Junhui Zhou; Da Chen; Yanqiong Shen; Qizan Gong; Zhihao Li; Zunhao Zhou; Entao Li; Fangxu Li; Zekai Cheng; et al. (Proceedings of the National Academy of Sciences, 2026)
Several orthoebolaviruses have been established, including Orthoebolavirus zairense [for Ebola virus (EBOV)], Orthoebolavirus sudanense [for Sudan virus (SUDV)], and Orthoebolavirus bundibugyoense [for Bundibugyo virus (BDBV)]. Orthoebolaviruses are highly virulent pathogens that cause severe disease in humans. However, most existing vaccines primarily target EBOV, and fail to provide robust cross-protection against other lethal orthoebolaviruses. The development of a broad-spectrum vaccine has the potential to efficiently mitigate outbreaks caused by multiple orthoebolaviruses. In this study, we developed and evaluated a broad-spectrum mRNA vaccine, designated [GPs+NP]@LNP, formulated with a single lipid nanoparticle (LNP) platform to encapsulate a mixed mRNA payload encoding the glycoproteins (GPs) of EBOV, BDBV, and SUDV, along with the nucleoprotein (NP) of EBOV. This rational antigenic combination was designed to engage both humoral and cellular arms of the immune system. Consistent with this design, the compatibility of humoral immunity-driving GPs and cellular immune-dominating NPs supports complementary immune responses, which together are associated with broad and durable protection against EBOV, BDBV, and SUDV in animal models. Antigenic coordination within a single LNP formulation may therefore represent an effective strategy to optimize vaccine immunogenicity, protective effect, durability, and safety. Collectively, these findings highlight [GPs+NP]@LNP as a promising approach for the development of next-generation vaccines targeting multiple pathogenic orthoebolaviruses.